Aortic valve neocuspidization and its technical nuance. Issue 8 (9th May 2022) - Dhingra, Nitish K.; Verma, Subodh; Yanagawa, Bobby; Hibino, Makoto
Abstract: Aortic valve neocuspidization or Ozaki procedure represents an advanced surgical strategy for the management of patients with aortic valvulopathy. It has been shown to have clinical and hemodynamic outcomes that compare favorably with aortic valve replacement as it restores physiological aortic valve function and left ventricular remodeling. There are, however, a new set of issues including structural valve deterioration, leaflet tear/perforation, and need for reoperation. A keen understanding of the technical nuances involved with the Ozaki procedure may help in reducing the incidence of such adverse outcomes.